Big data processing using Apache Spark - Lelek, Tomasz; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"In this course, we will learn how to leverage Apache Spark to be able to process big data quickly. We will cover the basics of Spark API and its architecture in detail. In the second section of the course, we will learn about Data Mining and Data Cleaning, wherein we will look at the Input Data Structure and how Input data is loaded In the third section we will be writing actual jobs that analyze data. By the end of the course, you will have sound understanding of the Spark framework which will help you in writing the code understand the processing of big data."--Resource description page.
Title from resource description page (Safari, viewed June 28, 2017).
Presenter, Tomasz Lelek.
Keywords: Spark (Electronic resource : Apache Software Foundation); Big data; Data mining; Information retrieval; Electronic books